A streamlined method to determine the antibiotic resistance of plaque-forming predatory bacteria - Wülbern, Janna; Carstensen, Yvonne; Buchholz, Florian; Schulenburg, Hinrich; Johnke, Julia (Frontiers in Microbiology, 2025)
IntroductionAntimicrobial resistance (AMR) is a critical global health issue caused by antibiotic overuse, leading to the rise of multi-resistant pathogens such as in bacteria of the ESKAPE group. Alternative or combination therapies, including bacteriophages and plaque-forming predatory bacteria, are being explored in response. Bdellovibrio bacteriovorus, a Gram-negative bacterial predator belonging to the Bdellovibrio and like organisms (BALOs), can kill other Gram-negative bacteria after the periplasmic invasion, including multidrug-resistant pathogens. However, a combined treatment of antibiotics and plaque-forming predatory bacteria requires the predatory bacteria to be resistant to the antibiotic. The predator’s unique growth requirements limit standardized AMR testing methods.Materials and methodsWe propose a streamlined three-step protocol to measure AMR in plaque-forming predatory bacteria. It requires the (i) cultivation of a dense Bdellovibrio culture with a suitable prey strain, followed by (ii) a double-layered agar plaque assay using a prey strain resistant to the antibiotic of interest, and (iii) the application of E-test strips for minimum inhibitory concentration (MIC) determination. We apply the method to the commonly used strain B. bacteriovorus HD100. We use P. aeruginosa H03 as prey for MIC determination for five antibiotics.ResultsOur results show consistent MICs for B. bacteriovorus HD100 across independent experiments. Reliable MIC determination for meropenem was limited by P. aeruginosa H03 susceptibility to this antibiotic. Further, we observed a positive association between MIC values and predator inoculum concentration for ceftazidime, ciprofloxacin, and gentamicin. Prolonged incubation time increased MIC values, notably for ciprofloxacin. While resistant to piperacillin, predator plaques were absent on plates with piperacillin-tazobactam combinations.ConclusionThe streamlined approach described here to determine MICs in plaque-forming predatory bacteria proves effective and robust, when using a suitable (i.e., resistant) prey. It provides a starting point for the joint study of antibiotics and plaque-forming predatory bacteria.